THE IMPLEMENTATION OF EDMODO FOR TEACHING WRITING RECOUNT TEXT TO THE TENTH GRADERS OF MAN KUNIR (RETAIN, 2016)
THE IMPLEMENTATION OF EDMODO FOR TEACHING WRITING RECOUNT TEXT TO THE TENTH GRADERS OF MAN KUNIR Ifatus Sholihah English Department, Languages and Arts Faculty, The State University of Surabaya Email:ifatussholihah@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Department, Languages and Arts Faculty, The State University of Surabaya Email:pungki_unesa@yahoo.co.id Abstract This study used descriptive qualitative as the research method to know the students’ ability in writing recount text by using Edmodo. In this study, the researcher observed how the teacher implement Edmodo for teaching writing recount text, the students’ result writing, and the students’ response toward the implementation of Edmodo. This study conducted totenth graders of MAN Kunir, Blitar. Based on the result of the study, it can be concluded that the implementation of Edmodo could help the students to improve their writing ability especially in writing recount text.Besides, the result of students’ writing recount text belongs to good category. Generally, students give the positive response toward the implementation of Edmodo for teaching writing recount text. Keywords:Writing Ability, Recount Text, Edmodo Abstrak Penelitian ini menggunakan metode kualitatif deskriptif untuk mengetahui kemampuan siswa dalam menulis teks recount. Pada penelitian ini, peneliti mengobservasi bagaimana guru menerapkan Edmodo untuk mengajar menulis teks recount, hasil menulis siswa, dan respon siswa terhadap penerapan Edmodo. Penelitian ini di terapkan kepada murid kelas sepuluh MAN Kunir, Blitar. Berdasarkan hasil analisis penelitian ini, dapat disimpulkan bahwa penerapan Edmodo dapat membantu meningkatkan kemampuan meulis siswa terutama dalam menulis teks recount. Disamping itu, hasil dari menulis teks recount siswa dikategorikan dalam kategori bagus. Secara umum, murid memberi tanggapan yang bagus terhadap penerapan Edmodo untuk mengajar menulis teks recount. Kata Kunci: Kemampuan Menulis, Teks Recount, Edmodo